Sistem Informasi Pengelolaan Surat Masuk Dan Surat Keluar Di STMIK AUB Surakarta - Joko Agus Prawono; Anton Respati Pamungkas (INFORMATIKA, 2015)
The most practical and efficient system in handling incoming and outgoing mail is to use pengagendaan number system, so every incoming and outgoing mail both internally and externally can be recorded in the agenda. Numbering (coding) letter done in order to know how many letters have been circulating in the activities of a company or organization. The system is made in this paper to record all incoming mail received, automation numbering outgoing mail, appointment letter and invitation creation is integrated into the application MsWord. Integration into MsWord, letter format changes can be done easily. Outputs of this system besides outgoing mail through MsWord also mnghasilkan letter category list, the list of incoming mail and outgoing mail per period. PIECES methods used to analyze the weaknesses of the current system, as well as analyze the needs of the system being developed. In the design of the system is developed flowchart system, data flow diagram, design inputs, design outputs and database design. The system is build by using Visual Basic programming language. Keywords : incoming and outgoing mail, MsWord integration, STMIK AUB Surakarta